Increasing blink rates: Reducing dried eye symptoms with eye rest-break application - Dian D.I., Daruis; Hairunnisa, Osman; Ezrin Hani, Sukadarin; Fauzana, Mustaffa; Ardimansyah, Henderi; Zulkefli M., Sain; Azmir, Ariffin; Siti N.A., Jamaludin; Baba M., Deros (Malaysian Public Health Physicians’ Association, 2020)
Long working hours with video display unit without appropriate breaks could drain the eyes. This study intends to investigate the efficiency of eye rest-break application to reduce dried eye symptoms by increasing blink rates. Blink rates and dried eye symptoms score among laboratory workers before and after the implementation of eye rest-break application were compared. The numbers of blink rates were recorded using a webcam for 5 minutes without the subjects aware when the recording starts or ends. Then, the Ocular Surface Disease Index (OSDI) was used to measure the dried eye symptoms. For eyes rest-break, EyeLeo© application was used. It is computer application that gives reminders to video display unit (VDU) users to take short breaks for their eyes. Six laboratory workers who are constantly working with VDU were selected as subjects. Data was analysed using Wilcoxon Signed-Rank Test, to test the comparison between variables before and after intervention by reporting its median (inter quartile range, IQR). The findings showed that the median after intervention (39.5, 10) is significantly higher (p-value = 0.028) than the median before intervention (7.3, 3). As for dried eye symptoms, median for Ocular Surface Disease Index after intervention (27.9, 8.9) is significantly lower (p-value = 0.027) than the median before intervention (36.5, 9.4). As a conclusion, application such as EyeLeo© eye rest-break is a potential intervention and may be used to increase blink rates and reducing dried eye symptoms among visual display unit workers.